THE SPECIFICITY OF IMPLEMENTING THE VIENNA CONVENTION ON DIPLOMATIC RELATIONS IN DEFENSE (MILITARY) DIPLOMACY - Blagojević, Veljko (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Vienna Convention on Diplomatic Relations regulates the general framework for the implementation of diplomatic functions of State and other subjects of international law. Contemporary diplomacy is evolving in many areas that have not traditionally been in its focus, such as police and intelligence cooperation. The Republic of Serbia has also started appointing police and Security-Intelligence Agency representatives to diplomatic missions abroad, and it is essential that this issue is monitored and studied from the standpoint of legal regulation.It is clear that this matter is regulated by diplomatic and consular law, but also by national legislation and diplomatic practice. The experience and tradition of defense (military) diplomacy of the Republic of Serbia in adapting its functions to the Vienna Convention on Diplomatic Relations, legal regulation and organizational and functional support to the defense attachés network, as well as the procedures for selecting defense attachés, training and preparing them for the duty, as well as monitoring and directing them during the performance of the diplomatic service are indisputable at national level. The tradition of military diplomacy that lasts more than 140 years, indicates the level of diplomatic practice which allows us to conclude that Serbia does posses all the needed criteria for quality and functional implementation of the assigned tasks.The question is how these criteria are met in the newly formed network of diplomatic representations of the Police and the Security-Information Agency, bearing in mind the extremely negative experiences with economic representatives of the Republic of Serbia abroad. There is no doubt that their engagement is in line with international and national legislation, but the issue of the lack of diplomatic practice in organizational and functional terms remains a questionable one. Furthermore, there is the issue of their responsibilities within the diplomatic and consular missions and the harmonization of different professional cultures and ethics, as well as the preparation for performing their duties abroad. It is clear that all these problems cannot be solved in the short term, which is a relatively new organizational solution. Simply, it has to take some time to detect shortcomings in practice and generate the experience necessary to overcome them. The practice of organizing defense (military) diplomacy of the Republic of Serbia can certainly serve as a signpost for their resolution, while respecting the specificities arising from different responsibilities and professional ethics.By analyzing the specifics of the implementation of the Vienna Convention on Diplomatic Relations in defense (military) diplomacy, analogies can be seen with the defining functions, and its legal and organizational experiences can serve as a guide to regulating the functions of Police and Security-Intelligence Agency representatives in the diplomatic service.
Keywords: diplomacy; Defence Diplomacy of the Republic of Serbia; diplomatic law and practice; Vienna Convention on Diplomatic Relations; protocol